Copper removal from waste water by using rice husk activated carbon – a review - Hamidon, Nuramidah; Malik, Alia Farhana; Mohd Sunar, Norshuhaila; Muhamad, Mimi Suliza (Penerbit UTHM, 2020)
Agricultural waste is a waste that presents as a result of several agricultural processes. It covers muck and other waste from farms, harvest waste, fertilizer run-off and pesticides that enter into the water, air or soils [7]. The low cost of agriculture waste can be used to eliminate heavy metal from wastewater and that has been investigated by many researchers [11]. The agriculture waste that will discuss in this paper are rice husk ash. Rice husk is the harsh layer that covering rice grains and will be separated from the grains during the milling process. The husk is made from hard materials including silica and lignin to protect the seed during rice season. The husk usually indigestible for humans. Through the milling process, the husk will take out from the grain to form brown rice. Then, the brown rice will be milled further to take out the bran layer to become white rice [16]. Rice husk is the large quantities of waste available in all rice-producing countries and it contains about 30%, 50% of organic carbon..